Comparison of methods of functional group analysis using results from laboratory and field aerosol measurements. Issue 9 (19th July 2021) - Claflin, Megan S.; Liu, Jun; Russell, Lynn M.; Ziemann, Paul J.
Abstract: A study was conducted to compare two methods for analysis of functional groups in secondary organic aerosol (SOA) generated in the laboratory and organic aerosol collected in the Southeastern Oxidants and Aerosol Study (SOAS). Although not as widely used as molecular and elemental analysis, functional group analysis of filter samples provides chemically specific information that can be used to characterize organic aerosol sources, mechanisms of formation, and physical-chemical properties. Here, we compared measurements made using Fourier Transform Infrared (FTIR) spectroscopy, the most widely used method of functional group analysis, with those made using derivatization-spectrophotometric methods. When used to analyze SOA generated from a series of environmental chamber reactions, the methods agreed quite well when results were assigned to four groups: (1) functional groups that contain an O–H bond; (2) non-acid functional groups containing a C = O moiety; (3) organonitrate groups; and (4) alkane groups. Overall, the agreement between the two methods indicates that either is adequate for measuring the functional group composition of SOA. While the derivitization-spectrophotometric methods offer more specificity, they also require more time and aerosol mass for sample analysis than the FTIR methods. It was also shown that functional group signatures obtained from SOA generated in environmental chambers can potentially be used to gain insight into oxidation and particle-phase reactions responsible for SOA formation in field samples. Copyright © 2021 American Association for Aerosol Research